Robot‐assisted vs open radical cystectomy for bladder cancer in adults. (29th May 2020) - Rai, Bhavan Prasad; Bondad, Jasper; Vasdev, Nikhil; Adshead, Jim; Lane, Tim; Ahmed, Kamran; Khan, Mohammed S.; Dasgupta, Prokar; Guru, Khurshid; Chlosta, Piotr L.; Aboumarzouk, Omar M.
Abstract : Background: It has been suggested that, in comparison with open radical cystectomy (ORC), robot‐assisted radical cystectomy (RARC) results in less blood loss, shorter convalescence and fewer complications, with equivalent short‐term oncological and functional outcomes; however, uncertainty remains as to the magnitude of these benefits. Objectives: To assess the effects of RARC vs ORC in adults with bladder cancer. Search Methods: We conducted a comprehensive search, with no restrictions on language of publication or publication status, for randomized controlled trials (RCTs) that compared RARC with ORC. The date of the last search was 1 July 2018. Databases searched included the Cochrane Central Register of Controlled Trials, MEDLINE (1999 to July 2018), PubMed Embase (1999 to July 2018), Web of Science (1999 to July 2018), Cancer Research UK (www.cancerresearchuk.org/ ), and the Institute of Cancer Research (www.icr.ac.uk/ ). We also searched the following trial registers: ClinicalTrials.gov (clinicaltrials.gov/); BioMed Central International Standard Randomized Controlled Trials Number (ISRCTN) Registry (www.isrctn.com ); and the World Health Organization International Clinical Trials Registry Platform. The review was based on a published protocol. Primary outcomes of the review were recurrence‐free survival and major postoperative complications (Clavien grade III to V). Secondary outcomes were minor postoperative complications (Clavien grades I and II), transfusion requirement, length of hospital stay (days), quality of life, and positive surgical margins (%). Three review authors independently assessed relevant titles and abstracts of records identified by the literature search to determine which studies should be assessed further. Two review authors assessed risk of bias using the Cochrane risk‐of‐bias tool and rated the quality of evidence according to GRADE. We used Review Manager 5 to analyse the data. Results: We included in the review five RCTs comprising a total of 541 participants. Total numbers of participants included in the ORC and RARC cohorts were 270 and 271, respectively. We found that RARC and ORC may result in a similar time to recurrence (hazard ratio 1.05, 95% confidence interval [CI] 0.77 to 1.43; two trials, low‐certainty evidence). In absolute terms at 5 years of follow‐up, this corresponds to 16 more recurrences per 1000 participants (95% CI 79 fewer to 123 more) with 431 recurrences per 1000 participants for ORC. We downgraded the certainty of evidence because of study limitations and imprecision. RARC and ORC may result in similar rates of major complications (risk ratio [RR] 1.06, 95% CI 0.76 to 1.48; five trials, low‐certainty evidence). This corresponds to 11 more major complications per 1000 participants (95% CI 44 fewer to 89 more). We downgraded the certainty of evidence because of study limitations and imprecision. We were very uncertain whether RARC reduces minor complications (very‐low‐certainty evidence). We downgraded the certainty of evidence because of study limitations and very serious imprecision. RARC probably results in substantially fewer transfusions than ORC (RR 0.58, 95% CI 0.43 to 0.80; two trials, moderate‐certainty evidence). This corresponds to 193 fewer transfusions per 1000 participants (95% CI 262 fewer to 92 fewer) based on 460 transfusion per 1000 participants for ORC. We downgraded the certainty of evidence because of study limitations. RARC may result in a slightly shorter hospital stay than ORC (mean difference −0.67, 95% CI −1.22 to −0.12; five trials, low‐certainty evidence). We downgraded the certainty of evidence because of study limitations and imprecision. RARC and ORC may result in a similar quality of life (standardized mean difference 0.08, 95% CI 0.32 lower to 0.16 higher; three trials, low‐certainty evidence). We downgraded the certainty of evidence because of study limitations and imprecision. RARC and ORC may result in similar positive surgical margin rates (RR 1.16, 95% CI 0.56 to 2.40; five trials, low‐certainty evidence). This corresponds to eight more (95% CI 21 fewer to 67 more) positive surgical margins per 1000 participants, based on 48 positive surgical margins per 1000 participants for ORC. We downgraded the certainty of evidence because of study limitations and imprecision. Conclusions: We conclude that RARC and ORC may have similar outcomes with regard to time to recurrence, rates of major complications, quality of life, and positive surgical margin rates (all low‐certainty evidence). We are very uncertain whether the robotic approach reduces rates of minor complications (very‐low‐certainty evidence), although it probably reduces the risk of blood transfusions substantially (moderate‐certainty evidence) and may reduce hospital stay slightly (low‐certainty evidence). We were unable to conduct any of the preplanned subgroup analyses to assess the impact of patient age, pathological stage, body habitus, or surgeon expertise on outcomes. This review did not address issues of cost‐effectiveness.